3=6-3n

Simple and best practice solution for 3=6-3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=6-3n equation:



3=6-3n
We move all terms to the left:
3-(6-3n)=0
We add all the numbers together, and all the variables
-(-3n+6)+3=0
We get rid of parentheses
3n-6+3=0
We add all the numbers together, and all the variables
3n-3=0
We move all terms containing n to the left, all other terms to the right
3n=3
n=3/3
n=1

You can always share this solution

See similar equations:

| 5(3-y)=20 | | x³-9x+1=0 | | 6x+14=11x-31 | | X/3x=8 | | 2^3m+3=16^2m-3 | | 5x-21=-9x+21 | | 5x^2=1/20 | | -1-8x=143 | | 36-7x=-15-5-7 | | 2x?9=16 | | (y2-y-2/5y)(10y/y+1)=(y2-y-2)(10y)/(5y)(y+1) | | 8^-6k-7=8^k+7 | | 0.04(12)+0.01m=0.02(12+m) | | 3*t+5=2 | | -1-4+b=-4+2b | | –2m=8?m | | 2r+6=10r-10-6r | | 8x-3x+4=-5x+4 | | -4-5g=-4g+6 | | 6=8+(p)/(4) | | 6-7x=-2x+8-3 | | -8m+9=-6m-7 | | 14+x=5x | | 4n+9=-15 | | 110°+3x+11=16x+4 | | -1/3-g=1/3 | | -9f+5+1=9-10f | | p=p-11 | | -2w+10=2w-10 | | x3=-48 | | -10-2j=-4j+8+8j | | 3c+5=4c-1 |

Equations solver categories